Book publishing and local government: the history of relations between publishers and regional administrations in Siberia and the Far East in the 90-ies of XX – 10-s of XXIst century - A. L. Posadskov (Библиосфера, 2019)
The article summarizes the historical experience on support of the Siberian and Far Eastern regional book publishing by regional and national republican authorities and management in the late twentieth – early twenty-first century. During 25 years regional administrations have passed a long way from unskillful attempts to copy the support measures practiced at the Federal center, from the single support of individual publications to an elaborate system of assistance for authors and publishers producing socially demanded books, mainly of local and regional content. The author considers the historical evolution of this process – development of management decisions on financing local publishing proposals aimed at strengthening the cultural, scientific and creative potential of the regions in the East of Russia. The classification, characteristics and evaluation of each of the forms for publishing support used in the regional practice are given. The author has come to conclusion that the best examples of publishing projects effective assistance are the activity of Omsk region and Krasnoyarsk Krai administrations. The former has the support model, in which distribution of funds is based on the publishing program of the regional Ministry of culture. In the latter the funds are allocated in the form of social grants to the regional winners of the annual contest “Book Krasnoyare”, that is fixed in its regional legislation as the protected item of expenditure. It is stated that not all administrations in the regions of Siberia and the Far East are concerned about the development of local publishing. In many regions the forms and level of support for the publishing environment do not meet the needs of society, remain unchanged since the end of the twentieth century.